0.5(14x-4y+12)= 0
hope this helped!
2f(x) = 2x - 4 [0, 3]3f(x) = 3x - 1 [-2, -1]9f(x) = x² [4, 5]4f(x) = 4x [5, 20]5f(x) = x² - 3 [0, 5]1f(x) = x + 10 [-5, -1]10f(x) = 10x [-3, 0]¹/₂f(x) = 0.5x - 2 [2, 4]11f(x) = 2x² + x [1, 4]-1f(x) = -x + 2 [-3, 5]Domainthe set of all reasonable input values of x for the functionRangeset of output y values for the domain of the functionAverage Rate of ChangeChange in values over a given interval.Origin(0,0) on the coordinate graphing system; where the two axes meetx-axisthe horizontal number line in the coordinate systemy-axisthe vertical number line in the coordinate systemCoordinatesany specific (x,y) in the coordinate systemx-interceptwhere the function intersects the x-axisy-interceptwhere the function intersects the y-axis; the b value in a linear functionLinear FunctionA function whose graph is a straight line, where the average rate of change (slope) is constant.Exponential FunctionA function where the average rate of change is not constant and whose input value is an exponent.Table of ValuesA table showing two sets of related numbers<span>Slope of line through the points (-2, 3) and (0,0)
m = (0 - 3) / (0 - -2) = -3/2</span><span>Average Rate of Change on the interval
[-2, 0]</span>Slope: m = "rise over run" = 2Rate of Change<span>Slope of line through the points (5, -1) and (0,0)
m = (0 - -1) / (0 - 5) = -1/5</span><span>Average Rate of Change on the interval
[0, 5]</span><span>Slope of line through the points
(0, 16) and (4, 21)
m = (21 - 16) / (4 - 0) = 5/4</span>Average Rate of Change over the interval [0,4]
Here's the solution :
- Side of the equilateral triangle = x
perimeter of equilateral triangle = 3 × x = 3x
perimeter of square = 4 × (x + 10)
now, according to above statement :
permission (square) = 3 × perimeter (triangle)
that is :
therefore, side of triangle = 8 cm
- perimeter (triangle) = 8 × 3 = 24 cm
- side of square = 8 + 10 = 18 cm
- perimeter of square= 18 × 4 = 72 xm
Answer:
The remainder = 13.
Step-by-step explanation:
By the Remainder Theorem the remainder when the function is divided by
x - 1 is f(1).
f(1) = 4(1)^3 + 4(1)^2 + 2(1) + 3
= 4 + 4 + 2 + 3
= 13.
So x - 1 is not a factor of f(x).
If it was a factor the remainder would be 0.